Analisis implementasi pendidikan seni tari berdasarkan teori pendidikan kesenian Ki Hadjar Dewantara di sekolah dasar - Martini, Adis Eva; Matsuri, Matsuri; Ardiansyah, Roy (Didaktika Dwija Indria, 2023)
Art education is effectively implemented for elementary school students regarded the formation of learning circumstances that provide chances for children in an effort to develop a child's sense of sensitivity, imagination, and creativity, but remain under control. The research was conducted to find out the relevance between the current art education with Ki Hadjar Dewantara's art education ideology. The research was conducted with the subjects of grade 2 elementary school students and class teachers. The method used in the research is descriptive qualitative method with triangulation data collection techniques, namely observation, interviews, and documentation studies. The results of the research are that the teacher not only teaches the dance, but also the values comprised in the dance so that students can understand the message or content conveyed from the dance, even though students have not been able to convey messages to the audience through non-verbal movements. There are three aspects that must be fulfilled, namely Wiraga, Wirama and Wirasa. However, two of those aspects, wirama and wirasa, have not been maximized. Not all learners are able to harmonize movements with the rhythm, and live the dance movements performed.